Herding differently: A level-k model of social learning - Stefan P. Penczynski (University of Mannheim, Department of Economics, 2013)
This paper proposes a behavioral model of social learning that unies various forms of inferential reasoning in one hierarchy of types. Iterated best responses that are based on uninformative level-0 play lead to the following of the private information (level-1), to the following of the majority (level-2), to a differentiated view on predecessors (level-3), etc. I present evidence from three sources that these are the prevalent types of reasoning in social learning: a review of social learning studies, existing data from Celen and Kariv (2004) as well as new experimental data that includes written accounts of reasoning from incentivized intra-team communication.
urn:nbn:de:bsz:180-madoc-326677
Keywords: C91; D82; D83; D84; 330; Social learning; levels of reasoning